209k views
2 votes
Which of the following is a solution of 3x2 = 7x − 3 quadratic equation

User RogerV
by
4.8k points

1 Answer

4 votes

For this case we have the following quadratic equation:


3x ^ 2-7x + 3 = 0

The solutions will be given by:


x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2a}

Where:


a = 3\\b = -7\\c = 3

Substituting the values we have:


x = \frac {- (- 7) \pm \sqrt {(- 7) ^ 2-4 (3) (3)}} {2 (3)}\\x = \frac {7 \pm \sqrt {49-36}} {6}\\x = \frac {7 \pm \sqrt {13}} {6}

We have two roots:


x_ {1} = \frac {7- \sqrt {13}} {6}\\x_ {2} = \frac {7+ √(13)} {6}

ANswer:


x_ {1} = \frac {7- \sqrt {13}} {6}\\x_ {2} = \frac {7+ √(13)} {6}

User Frank Hoffman
by
5.6k points